2014
DOI: 10.1111/ases.12155
|View full text |Cite
|
Sign up to set email alerts
|

Is mechanical bowel preparation still necessary for gynecologic laparoscopic surgery? A meta‐analysis

Abstract: Our results suggest that routine use of MBP for gynecologic laparoscopic surgery should not be recommended. However, additional randomized controlled trials using large samples are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Meta-analyses[ 8 - 12 ] have been published on MBP in elective colorectal surgery showing mixed results, with most studies demonstrating no difference in infective complications between patients receiving MBP or control treatment, although control treatment varied significantly between the use of a rectal enema or absolutely no preparation. Similar results have been found in gynaecological[ 13 , 14 ] and urological[ 15 , 16 ] surgery where studies have shown no benefits in visualisation, bowel handling or complication rates between patients treated with bowel preparation and those given no bowel preparation. As a result of this inconclusive evidence, several studies have established that practice varies significantly between countries, and even surgeons in the same institution[ 17 , 18 ].…”
Section: Introductionsupporting
confidence: 82%
“…Meta-analyses[ 8 - 12 ] have been published on MBP in elective colorectal surgery showing mixed results, with most studies demonstrating no difference in infective complications between patients receiving MBP or control treatment, although control treatment varied significantly between the use of a rectal enema or absolutely no preparation. Similar results have been found in gynaecological[ 13 , 14 ] and urological[ 15 , 16 ] surgery where studies have shown no benefits in visualisation, bowel handling or complication rates between patients treated with bowel preparation and those given no bowel preparation. As a result of this inconclusive evidence, several studies have established that practice varies significantly between countries, and even surgeons in the same institution[ 17 , 18 ].…”
Section: Introductionsupporting
confidence: 82%
“…Regardless of the type of procedure (laparoscopy, robotic, or vaginal surgery), routine administration of MPB seems to offer no advantage to any of the objectives mentioned above [24][25][26]. Surgical field visualization is irrelevant to the type of preoperative bowel preparation [25], bowel handling is the same whether MBP is used or not, surgical site infection rates are not affected by MBP use [26], LOS is not increased when MBP is omitted 4 e Scientific World Journal [9,19], while patients' discomfort and adverse physiologic effects are significantly higher when oral laxatives are used [24,25]. e most common MBP regimens include the use of laxatives which are administered either orally or rectally [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical field visualization is irrelevant to the type of preoperative bowel preparation [25], bowel handling is the same whether MBP is used or not, surgical site infection rates are not affected by MBP use [26], LOS is not increased when MBP is omitted 4 e Scientific World Journal [9,19], while patients' discomfort and adverse physiologic effects are significantly higher when oral laxatives are used [24,25]. e most common MBP regimens include the use of laxatives which are administered either orally or rectally [24,25]. Sodium phosphate (NaP) can be used either as an enema or as an oral preparation, while polyethylene glycol is used orally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The routine use of MBP for gynecologic laparoscopic surgery has not been recommended [3], but some questions remain to be answered. No controlled trial in the literature has compared the effects of MBP with oral sodium phosphate (NaP) vs. NaP enema with respect to intraoperative visualization of the surgical field, ease of bowel handling, and overall ease of surgery.…”
mentioning
confidence: 99%